DAMPAK ESG DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN, DIMODERASI KEPEMILIKAN ASING - Sitinjak, Elizabeth Lucky Maretha; Warastuti, Yusni; Djati Sasmito, Y. Wisnu (Bina Ekonomi, 2025)
ESG dimensions and recognizing the strategic role of foreign ownership in shaping market perceptions. This study aims to examine the effect of Environmental, Social, and Governance (ESG) scores and financial performance on value of the firm, and to assess the moderating role of foreign ownership in Indonesian capital market. The sample consists of 80 publicly listed companies in Indonesia Capital Market that have ESG scores available for the period 2021 to 2023. Firm valuation is measured by Price to Book Value (PBV), while the independent variables include Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and ESG components: Environmental Score (ENV), Social Score (SOC), and Governance Score (GOV), along with the aggregated ESG Score. The analysis was conducted using EViews-13 and panel data regression models, including both Fixed Effect and Moderated Regression Analysis. The findings indicate that ROA, ENV, SOC, and GOV scores have a positive and significant effect on firm value. Interestingly, the aggregated ESG Score shows a significant negative effect on PBV, suggesting possible distortion when sustainability dimensions are not assessed individually. CR has a negative significant effect, while DER shows a positive significant effect before moderation. After including foreign ownership as a moderating variable, the influence of CR, DER, and ESG Score becomes statistically insignificant, indicating that foreign investors tend to neutralize the effect of liquidity, leverage, and overall ESG disclosures. This study highlights the importance of disaggregating